Multiple sclerosis starting before the age of 18 years: the Brazilian experience - Yara Dadalti Fragoso; Maria Lucia Brito Ferreira; Nivea de Macedo Oliveira Morales; Walter Oleschko Arruda; Joseph Bruno Bidin Brooks; Denise Sisterolli Diniz Carneiro; Margarete de Jesus Carvalho; Elizabeth Regina Comini-Frota; Eber Castro Correa; Carlos Augusto de Albuquerque Damasceno; Renan Barros Domingues; Alessandro Finkelsztejn; et al. (Arquivos de Neuro-Psiquiatria)
Multiple sclerosis (MS) starting in childhood and adolescence poses a challenge for diagnosis and management of the disease. The aim of the present study was to assess the characteristics of early onset MS in Brazilian patients. Methods Retrospective data collection from specialized MS units. Results From 20 MS units in 11 Brazilian states, 117 cases of MS starting before the age of 18 years were collected. These patients had an average of 10 years of disease duration, still typically with low disability and one relapse every 2.5 years. The mean age for disease onset was 13.7 years. Conclusion The present study introduces a large series of Brazilian cases of pediatric MS. Although some patients presented a very severe form of MS, on the whole the group of patients with MS starting in childhood or adolescence presented a relatively mild form of this disease in Brazil.